Fractional stochastic differential equation with discontinuous diffusion. Issue 6 (2nd November 2017) - Garzón, Johanna; León, Jorge A.; Torres, Soledad
ABSTRACT: In this article, we study a class of stochastic differential equations driven by a fractional Brownian motion with H > 1/2 and a discontinuous coefficient in the diffusion. We prove existence and uniqueness for the solution of these equations. This is a first step to define a fractional version of the skew Brownian motion.